PEMBERANTASAN PENYAKIT MASYARAKAT OLEH SATUAN POLISI PAMONG PRAJA DITEMPAT HIBURAN MALAM DI WILAYAH HUKUM KABUPATEN ROKAN HULU - Rival Nopiri; Erdianto '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Many people the disease occurred in recent years, the crime of msyarakat diseases include, intoxicating drinks (non-alcoholic), debauchery or prostitution, racketeering, porn action, entertainment bands and solo organ and so forth. The deeds bertentengan with legal norms and the norms that exist in the community occurred in almost all regions of Rokan Hulu. Facts on the ground are also stating so, the number of offenders who successfully secured by municipal police Rokan Hulu.This type of research is classified in sociological research. The source of data is secondary data, primary data and tertiary. In sociological or empirical research, the use of the method of qualitative analysis is a way of analyzing databerdasarkan concept, theory, thesis, legislation, expert views or views their own sentences. In conclusion method can be used deductive method. Taken special kedata common data and made conclusionsFrom the research, first, the setting on the crime of society's ills in the Criminal Code can not be used as a powerful weapon in ensnare offenders. That is why Rokan upstream membut Rule The terrain itself specifically to catch the offender penaykit society Local Ordinance No. 1 of 2009 on the Prohibition and Eradication of Diseases Society Second, the Civil Service Police Unit as enforcers Regional Regulation is not yet fully run its course, this is evidenced by yet their society's ills actors in Rokan Hulu is getting punishment or sanctions in accordance with what has been mentioned in the Regional Regulation No. 1 of 2009 on the Prohibition and Communicable disease society. So the disease community in Rokan Hulu is high. Supposedly, the Civil Service Police Unit in Rokan Hulu's ability to take decisive and thorough in giving sanctions to perpetrators of criminal acts of society's ills is in accordance with the sanctions that have been written in the Regional Regulation No. 1 of 2009 on the Prohibition and Control of Disease community. If not implemented in accordance with what has been written in the law the act ills of society in Rokan Hulu will be more widespread in the midst of public life.Keywords: social ills - criminal acts - Unit Police Civil Service